Bioinspired microstructure-reorganized behavior of carbon nanotube yarn induced by cyclic stretching training. Issue 1 (3rd December 2019) - Wang, Zhiyong; Wu, Jianhua; Wei, Xiaoxiao; Saleemi, Sidra; Liu, Wei; Li, Wei; Marriam, Ifra; Xu, Fujun
Abstract : Microstructure-reorganized behavior is where the microstructure of a material can be reorganized under some conditions, such as temperature or moisture changes, electrical or mechanical stimulation. Abstract : Microstructure-reorganized behavior is where the microstructure of a material can be reorganized under some conditions, such as temperature or moisture changes, electrical or mechanical stimulation. Human muscle, comprising an exceptional hierarchical structure, is a representative example whose flexibility and strength can be enhanced remarkably after cyclic stretching training owing to the mechanically reorganized structural arrangement and redistribution (alignment and elongation). The hierarchical structure (bundles and threads) of the yarn, which is similar to that (thick and thin filaments) of human muscle, can also be microstructure-reorganized. Herein, bioinspired by the structure-reorganized behavior of muscle, for the first time, a novel strain engineering strategy (cyclic stretching or cyclic loading) is adopted to tune the hierarchical structure and properties of CNT yarns. By applying an optimized tensile strain (10%) for cyclic stretching, the CNT yarn exhibits much enhanced mechanical and electrical properties of tensile strength (+64%), Young's modulus (+148%), conductivity (+30%) and piezo-resistive sensitivity (+35%), as compared with pristine CNT yarn. Moreover, a comprehensive structural mechanism is proposed and confirmed to interpret the microstructure-reorganized mechanism. The microstructure-reorganized CNT yarn can be generally applied in advanced wearable textiles, flexible electronics and multifunctional composites with much improved mechanical and electrical performance especially, under cyclic loading conditions.